2008
DOI: 10.1177/107327480801500309
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a Patient Navigator Program to Reduce Cancer Disparities in the American Indian Communities of Western South Dakota: Initial Observations and Results

Abstract: Early findings suggest that patient navigation is a critical component in addressing cancer disparities in this population. The program has established trust with individual cancer patients, with the tribal councils, and with the general population on each of the three reservations of western South Dakota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(110 citation statements)
references
References 10 publications
2
107
0
1
Order By: Relevance
“…First Nations People, M etit and Inuit living in Nunavut must travel a minimum of 2000 km by air to receive specialty care [26]. This geographical barrier and the requirements of transportation and temporary housing fall are analogous to that in LMICs [27].…”
Section: 'Global Health' Needed Within Highincome Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…First Nations People, M etit and Inuit living in Nunavut must travel a minimum of 2000 km by air to receive specialty care [26]. This geographical barrier and the requirements of transportation and temporary housing fall are analogous to that in LMICs [27].…”
Section: 'Global Health' Needed Within Highincome Countriesmentioning
confidence: 99%
“…Walking Forward is a superb example of a multifaceted programme that was developed through funding from the National Cancer Institute's Cancer Disparities Research Partnership. Through an emphasis on cancer education, patient navigation and clinical trial participation, Walking Forward addresses the barriers that prevent Lakota Sioux in the region surrounding Rapid City, South Dakota from being diagnosed with cancer at earlier stages and achieving optimal cancer outcomes [27,28]. To overcome deeply engrained mistrust of clinical trials, Walking Forward works with tribal councils, develops culturally sensitive consents, translates trial information into Lakota, and has created local employment opportunities for culturally competent staff members, many of whom grew up and still live on the reservations.…”
Section: 'Global Health' Needed Within Highincome Countriesmentioning
confidence: 99%
“…3,[14][15][16][17][18] The program employed community-based PN to deliver culturally appropriate community education about the value of screening and early detection and research. These PN played an important cultural role in developing a rapport with the community and reducing resistance to community engagement in clinical care and research activities.…”
Section: E92 Lj Whop Et Almentioning
confidence: 99%
“…18 Participants undergoing cancer treatment received around $1000 to assist with food, transportation and lodging. 15 Participants undergoing treatment had on average 15 (range 1 to 95) interactions with the PN and participants in the post-treatment follow-up phase of care received on average four (range 1-26) PN interactions. 15 A PN interaction was defined as a person-to-person contact or telephone call.…”
Section: E92 Lj Whop Et Almentioning
confidence: 99%
“…A review of patient navigator programmes for Indigenous patients (Whop et al, 2012) identified two programmes, Native Sisters Program and Walking Forward Program, that have positively contributed to improve outcomes to patients by increasing adherence to breast screening and reducing delays to treatment. While several Patient Navigation interventions (Burhansstipanov et al, 1998;Kanekar & Petereit, 2009;Petereit et al, 2008) have been implemented, only a few have been evaluated through randomised clinical trials (RCTs), and have included Indigenous cancer patients (Braun et al, 2015;Dignan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%